Maximum anaerobic power in adult Alpine ski racers - Miura, T. (International Journal of Sport & Health Science, 2015)
Alpine ski competition demands high-power output. However, the target maximum anaerobic power (MAnP) on a bicycle ergometer and its relationship to competitive performance has not yet been clarified for adult alpine ski racers. The aim of this study was to determine the target MAnP of adult alpine ski racers and its relationship to their performance. Participants included 14 male and 10 female alpine ski racers, who had graduated from high school. The MAnP was divided by the participant's weight to determine relative power to body weight (BW). Competitive performance was assessed in terms of the number of points on the International Ski Federation (FIS) slalom (SL) and giant slalom (GS). Both male and female racers showed either significant or marginally significant correlations (r= -0.40 to -0.69) of MAnP and MAnP/BW with the FIS SL and GS point totals. These results indicated that there was a relationship between MAnP and MAnP/BW and alpine ski competitive performance at the national level for both male and female competitors. In this study, the targets of the MAnP and MAnP/BW in FIS SL and GS were approximately 1300 W and 17 W/kg for males, and 900 W and 15 W/kg for females, respectively. These values are appropriate indicators of competitive performance.